Effective regulatory institutions for air transport: A European perspective - Hans-Martin Niemeier (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
The heated debate on the regulatory framework for airports has highlighted the importance of creating good institutions for air transport in general. This paper defines the concept of effective regulatory institutions for air transport. It also describes the value chain for air transport and how the state intervenes with what type of regulatory institution. The paper concludes by highlighting the institutional reforms necessary to make regulation effective.
Keywords: 330; Luftverkehr; Luftverkehrspolitik; Regulierung